Peran Metode Demonstrasi dalam Pengembangan Keterampilan Praktis Siswa di Bidang Teknologi - Nur Zakia Zahra; Wahyuni Fitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the era of the Industrial Revolution 4.0, skills are very important in the world of work, especially in the field of technology. However, many educational institutions still focus on theoretical learning, so that graduates are less prepared to face the demands of the world of work. This study aims to improve the effectiveness of methods to improve students' practical skills in the field of technology. This study uses a descriptive and quasi-experimental approach to collect data through observation, questionnaires, and practical skills tests. The results of the study show that this method has proven effective in improving students' practical skills, both in terms of technical mastery and conceptual understanding. However, limited resources and instructor capabilities are challenges in implementing this method. Therefore, a combination of compression methods with other approaches, such as project-based learning, is needed to provide a more holistic experience for students.